Impact of Inclusion of Multicomponent Synbiotic Russian Holstein Dairy Cow's Rations on Milk Yield, Rumen Fermentation, and Some Blood Biochemical Parameters - Trukhachev, Vladimir I.; Buryakov, Nikolai P.; Shapovalov, Sergey O.; Shvydkov, Aleksandr N.; Buryakova, Maria A.; Khardik, Irina V.; Fathala, Mohamed M.; Komarova, Oksana E.; Aleshin, Dmitrii E. (Frontiers in Veterinary Science, 2022)
The purpose of this study was to appraise the effect of the inclusion of multicomponent synbiotic “Kormomix® Rumin” in feeding lactating Holstein cows on milk productivity, indicators of rumen fermentation metabolism, and some hematological and biochemical parameters of the blood. For this study, 40 highly productive Russian Holstein cows were selected according to their productivity, physiological condition, live weight, and age. They were divided into four groups (10 heads/each). All animals received the basal total mixed ration (TMR), which was balanced and corresponded to the nutritional requirements for cows during the milking period with a milk yield of 36 kg/daily. The first group (control) fed basal (TMR) only while the 2nd, 3rd, and 4th group fed the basal (TMR) supplemented with a multicomponent synbiotic “Kormomix® Rumin” in amounts 25, 50, and 75 g/head/day, respectively, which was administered manually and individually after morning feeding daily and mixing carefully together with the concentrates directly after calving until 120 DIM. Milk, ruminal fluid, and blood samples were collected for studying the studied parameters. The highest values in all studied milk parameters were recorded in the 2nd experimental group but the differences were not significant. The inclusion of “Kormomix® Rumin” increased significantly the synthesis of volatile fatty acids in the 2nd experimental group (9.38 vs. 7.04 mmol/100 ml) in the control group. The level of serum α-Amylase (total) decreased significantly in the 2nd experimental group compared with other groups. The urea level recorded the lowest value in the control group, while the urea/creatinine ratio recorded the lowest value in the 4th group and the differences were significant when compared with the 2nd group. Accordingly, the inclusion of synbiotic “Kormomix® Rumin” in the diets of lactating cows has no impact on milk production. Whereas, it improves the intensity of rumen fermentation, which contributes to more efficient utilization of feed without any harmful effects on blood traits. Moreover, the recommended dose for use in their diets is 25 g/head/day.